The influence of human resource competency and entrepreneurial characteristics on the performance of small and medium industries - Rohman Willian; Husni Hasbullah; Fitri Widiastuti; Dahmiri Dahmiri (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2021)
The purpose of this study was to describe and analyze the influence of human resources competencies and entrepreneurial characteristics on the performance of the small-medium-sized food industry with the intervening variable of competitive advantage. This research is verification in nature, basically wants to test the truth of a hypothesis which is carried out through data collection in the field. The unit of analysis in this research is the food SMIs (Small and Medium Industries) actors in Jambi Province. The data were obtained through distributing questionnaires to 378 SMIs food entrepreneurs. The data analysis used was quantitative analysis using Structural Equation Modelling (SEM). The analysis results concluded that the respondents' responses to the variables of human resources competence, entrepreneurial characteristics, competitive advantage, and SMIs performance obtained the average number included in the good scale range. The variables of human resources competency, entrepreneurial characteristics, competitive advantage significantly influence the performance of food SMIs in Jambi Province, either partially or simultaneously. Human resources competency and entrepreneurial characteristics variables have a significant indirect effect on SMIs performance through the intervening variable of competitive advantage. The entrepreneurial characteristics variable is the dominant variable affecting the SMIs performance. The research model by adding the competitive advantage variable as an intervening variable resulted in a better effect on the SMIs performance.